2011
DOI: 10.1007/s10875-011-9572-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the ELANE Gene are Associated with Development of Periodontitis in Patients with Severe Congenital Neutropenia

Abstract: BackgroundPatients with severe congenital neutropenia (SCN) often develop periodontitis despite standard medical and dental care. In light of previous findings that mutations in the neutrophil elastase gene, ELANE, are associated with more severe neutropenic phenotypes, we hypothesized an association between the genotype of SCN and development of periodontitis.MethodsFourteen Swedish patients with SCN or cyclic neutropenia harboring different genetic backgrounds were recruited for periodontal examination. Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 62 publications
(59 reference statements)
1
72
0
1
Order By: Relevance
“…Congenital neutropenia (Kostman syndrome) is an inherited hematological disorder characterized by an arrest of PMN hematopoiesis at promyelocyte/myelocyte stage and absolute counts of <2000 cells/μL. Mutations in the ELANE gene coding for PMN elastase have been associated with periodontitis in patients with severe congenital neutropenia [41]. Gingivitis and severe periodontitis are common complications and despite some temporary improvement in PMN counts with granulocyte colony stimulating factor (G-CSF) treatment, patients with congenital neutropenia tend to have persistent gingivitis.…”
Section: Neutrophil Pathology In Periodontal Diseasesmentioning
confidence: 99%
“…Congenital neutropenia (Kostman syndrome) is an inherited hematological disorder characterized by an arrest of PMN hematopoiesis at promyelocyte/myelocyte stage and absolute counts of <2000 cells/μL. Mutations in the ELANE gene coding for PMN elastase have been associated with periodontitis in patients with severe congenital neutropenia [41]. Gingivitis and severe periodontitis are common complications and despite some temporary improvement in PMN counts with granulocyte colony stimulating factor (G-CSF) treatment, patients with congenital neutropenia tend to have persistent gingivitis.…”
Section: Neutrophil Pathology In Periodontal Diseasesmentioning
confidence: 99%
“…Ullbro evaluated an oral treatment protocol, which showed that compliance of the patient had a strong impact on the bleeding surfaces and pathological periodontal pockets. In the same study, it was revealed that there was no and P. gingivalis in periodontal pockets [72].…”
Section: Papillon-lefèvre Syndromementioning
confidence: 78%
“…The gene mutations seen are: ELANE gene encoding neutrophil elastase, which is more common in the dominant or sporadic forms of the disease [26], and in the recessive form the HAX1 gene, which encodes the mitochondrial antiapoptotic protein HS1-associating protein X-1 [70]. Patients with ELANE mutations seem to present more severe forms of periodontal disease compared to patients with HAX1 or unknown mutations [71,72]. It has been found that the neutrophils in these diseases can also have qualitative deficiencies, such as in the antimicrobial protein pro-LL-37 and reduced level of the human neutrophil peptide 1-3 in the granules, which means that their antimicrobial activity is reduced [73].…”
Section: Glycogen Storage Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early onset periodontitis frequently complicates congenital neutropenias, including severe congenital neutropenia (SCN), which is commonly associated with mutations in the gene encoding neutrophil elastase (25). Periodontitis in SCN correlates with excess IL-1β locally as well as with the oral microflora skewing toward more pathogenic organisms (26). It is conceivable that the absence of granule serine proteases and LL-37 from the neutrophils of PLS patients not only limits the array of antimicrobial effectors, but also undermines the proteolytic degradation of proinflammatory chemokines and cytokines necessary for tissue homeostasis, resulting in excess neutrophil recruitment and unchecked local inflammation (27).…”
Section: Conflict Of Interestmentioning
confidence: 99%